Case report: Joint deformity associated with systemic lupus erythematosus - Chen, Shu‐Lin; Zheng, Hui‐Juan; Zhang, Li‐Yu; Xu, Qiang; Lin, Chang‐Song (Immunity, Inflammation and Disease, 2022)
Objective Typically, Jaccoud arthropathy (JA) is characterized by joint deformation without bone erosion. However, some recent studies have shown that bone erosion also occurs in JA; however, this remains controversial. To date, there have been no unified diagnostic standards for JA. Herein, we report a case of systemic lupus erythematosus complicated with JA without bone erosion. Methods A 27‐year‐old woman was admitted to our department with a 2‐year history of pain, swelling, and progressive deformities of her hands and feet. She was diagnosed with systemic lupus erythematosus and class V lupus nephritis 5 years prior. Upon examination, her erythrocyte sedimentation rate and C‐reactive protein levels were found to be increased. She was positive for antinuclear antibodies, antidouble stranded DNA antibodies, and antiextractable nuclear antigen antibodies, with a decreased complement C3 and C4. Radiography and magnetic resonance imaging revealed no bone erosion. The patient was diagnosed with JA. She was treated with oral prednisone (10 mg daily), tofacitinib (5 mg twice daily), methotrexate (10 mg weekly), and celecoxib (0.2 g twice daily). Results The patient's joint symptoms improved after treatment. No further progress was observed during the 4‐month follow‐up period. Conclusion We believe that bone erosion is the key to distinguish rhupus syndrome from JA. However, this needs to be confirmed with further long‐term follow‐up studies. We found that the use tofacitinib, MTX, and celecoxib in combination with prednisone may be an effective regimen for the treatment of JA. We report a case of systemic lupus erythematosus (SLE) with Jaccoud's arthropathy (JA). We believe that SLE with erosive joint deformities should not be diagnosed as JA but rather as rhupus. We present this case to highlight the distinctions to consider during diagnosis, which would be of importance in clinical practice.